New roles of low density lipoproteins and vitamin E in the pathogenesis of atherosclerosis - (:unkn) unknown (My University, 1995)
Accumulation of oxidized low density lipoproteins in macrophages and smooth muscle cells causes foam cell formation, an initial step in atherosclerosis. Active oxygen species are considered important in the pathogenesis of the disease. Antioxidants, such as tocopherols and tocotrienols have been considered to prevent the deleterious effects of active oxygen species. We found native low density lipoproteins can stimulate directly smooth muscle cell proliferation, it is associated with an increase of protein kinase C activity. d-alpha-Tocopherol, biologically most active form of vitamin E, inhibits both cell proliferation and protein kinase C activity. The effect of d-alpha-tocopherol is not related to its radical scavenging properties. Transforming growth factor-beta secreted by smooth muscle cells as growth inhibitor. Low density lipoproteins decrease the release of transforming growth factor-beta from smooth muscle cells thus activating growth. d-alpha-Tocopherol activates the cellular release of transforming growth factor-beta. These new aspects explain the important role of low density lipoproteins and vitamin E in increasing and decreasing the risk of atherosclerosis, respectively.
Keywords: Humans; Animals; Rats; Molecular Sequence Data; Vitamin E; Transforming Growth Factor beta; Arteriosclerosis; Protein Kinase C; Cell Division; Amino Acid Sequence; Lipoproteins, LDL; Muscle, Smooth